Andragogia: Education in health for hygienization and cleaning agents as aid not controlling hospitary infection - Gomes Farias, Suzete; Bezerra Costa, Ana Vitória; Dutra Rocha , Andreza; de Oliveira Lima Neves, Madlene; de Souza Bezerra, Yago; Evangelista Brito, Gabriel; Oliveira da Fonseca, Iraide; Nascimento de Souza, Leandro; Nascimento Perrone, Maycon Victor; Portela de Azevedo, Arimatéia (Revista Feridas, 2022)
Introduction: Andragogy is a broad concept of human education and emerged from the need to have more specialized training for adults. Objective: To show the knowledge of hygiene and cleaning agents about biosafety and behaviors in a hospital environment before and after training and the results of health education aimed at them as an incentive to obtain assistance in the control of intra-hospital infections. Methodology: Retrospective, descriptive study with a quantitative approach, which used records of existing information on the variables found in spreadsheets stored in the database of the Hospital Infection Control Commission-CCIH referring to the results of pre and post written tests carried out during the training that took place with these servers. During these meetings, a practical test was also carried out to verify the skill of hand hygiene in the correct technique. Results: Information from tests applied to 125 servers were useful for the study. Their profile indicated that 50% had worked between 3 and 8 years in the profession and almost all (98%) had never received training on hygiene in hospital environments. About biosecurity, only 51% knew how to use PPE correctly. Conclusion: Their lack of technical knowledge can have a direct impact on performance during activities carried out in the work environment. Thus, the qualification of the team through health education will facilitate the process of breaking the chain of transmission of intra-hospital microorganisms.